2015
DOI: 10.1016/j.ejbas.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Propolis restored adiponectin level in type 2 diabetes through PPARγ activation

Abstract: Available online A B S T R A C TAdipose tissue regulates insulin sensitivity via the circulating adipocytokines, leptin, resistin and adiponectin. Hypoadiponectinemia contributes to the development of obesity and related disorders such as diabetes, hyperlipidemia, and cardiovascular diseases. In this study, we investigated the effects of Brazilian propolis on adiponectin levels in type 2 diabetes mellitus (T2DM), the mechanism of signaling pathway was explored as well. T2DM was induced in male Wistar rats usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Adiponectin is defined as an anti-diabetic hormone secreted by adipose tissue. It was associated with many metabolic disorders, including obesity, insulin resistance, obesity related cardiovascular and fatty liver diseases (35). Our data showed that treatment with MLE and MLP, created a significant increase in serum level of adiponectin.…”
Section: Discussionmentioning
confidence: 53%
“…Adiponectin is defined as an anti-diabetic hormone secreted by adipose tissue. It was associated with many metabolic disorders, including obesity, insulin resistance, obesity related cardiovascular and fatty liver diseases (35). Our data showed that treatment with MLE and MLP, created a significant increase in serum level of adiponectin.…”
Section: Discussionmentioning
confidence: 53%
“…It has been confirmed that there is a close link between oxidative stress and insulin resistance [ 28 ]. Inhibition of oxidative stress could be a potential approach to treat T2DM [ 29 ]. Increases in free radical level could initiate a decrease in insulin secretion in response to hyperglycemia, which could result in more serious hyperglycemia and diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations of adiponectin inversely correlate to weight, central obesity, risk of types 2 diabetes (T2D), and insulin resistance in humans [ 38 ]. Adiponectin promotes insulin sensitivity [ 39 ], fatty acid oxidation through activation of AMPK, p38-MAPK, and PPAR-α, and also enhances glucose uptake in the skeletal muscle [ 40 ].…”
Section: Adiponectin Functions In Different Body Organsmentioning
confidence: 99%
“…Diabetes mellitus is characterized by high glucose levels in the blood and is one of the serious conditions that affect other organs, such as kidneys, eyes, blood vessels, and nerves. Patients with diabetes mellitus type 2 represent about 90% of all diabetic patients [ 38 ].…”
Section: Adiponectin and Diseasesmentioning
confidence: 99%